University Instructors Use of, and Satisfaction with, Library Services in the Year Following the COVID-19 Outbreak / McClure, J. (2023). The COVID-19 pandemic and the rapid shift to an exclusively online format: Tracking online instructors’ utilization of library services over a year of virtual learning at the University of Memphis. College & Research Libraries, 84(1), 100–120. https://doi.org/10.5860/crl.84.1.100 - Miller-Nesbitt, Andrea (Evidence Based Library and Information Practice, 2023)
Objective – To determine online instructors' satisfaction with and level of use of library services during the year following the onset of the COVID-19 pandemic.Design – Survey questionnaire and follow-up interview.Setting – The University of Memphis (UofM) is a medium-sized, public, urban, R2 (doctoral university with high research activity) university. At the time of publication, UofM employed 930 full-time faculty and—through UofM Global—the option to earn degrees entirely online.Subjects – Survey respondents (n = 56) were online instructors at the University of Memphis.Methods – A confidential survey was distributed to all deans and department chairs at the UofM with instructions to disseminate the survey to all instructors teaching online course(s). Respondents were invited to participate in a follow-up interview.Main Results – Three common themes identified from the data were 1) respondents would have used the enhanced library services but were not aware of them; 2) respondents were very grateful for the services offered, in particular library instruction, Kanopy, and interlibrary loan; and 3) respondents did not feel like their courses would benefit from the library or its offered services.Conclusion – Based on the research results, the author concludes that the UofM Library must focus efforts on increasing visibility and communication, embedding the library in course design and assessment, as well as improving hybrid library instruction and offering purchase-on-demand collection development. The author has begun work on a follow-up study looking at ways to enhance the embedded librarianship service and increase communication between the UofM librarians and online teaching faculty.